Botany, Ethnobotanical Uses, Biological and Chemical Properties of Gethyllis afra L. (Amaryllidaceae) - Collen Musara; Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2019)
Gethyllis afra is an important medicinal plant species in South Africa. The current study critically reviewed the botany, ethnobotanical uses, biological and chemical properties of G. afra. Information on the botany, ethnobotanical uses, biological and chemical properties of G. afra was collected from multiple internet sources which included Scopus, Google Scholar, Elsevier, Science Direct, Web of Science, Pubmed, SciFinder and BMC. Additional information was gathered from pre-electronic sources such as journal articles, scientific reports, books and book chapters obtained from the University library. This study showed that G. afra is mainly used as food, aphrodisiac, and herbal medicine for colic, indigestion, stomach-ache, boils, bruises, insect bites, toothache, convulsions, heart problems and sleeplessness. Major compounds isolated from the fruits of G. afra include ?-pinene, n-butyl n-butyrate, isoamyl acetate, ?-pinene and 2-methylbutyl butyrate. There is need to validate the documented ethnomedicinal uses of G. afra through phytochemical and pharmacological studies. Therefore, future studies should focus on these knowledge gaps particularly evaluating the chemical and biological activities of G. afra crude extracts and compounds isolated from the species.